Existence and Uniqueness of Positive Solution for Boundary Value Problem of Fractional Differential Equations - Noora Housain; Hanan Mohammed; Nadia Abdulrazaq (Al-Rafidain Journal of Computer Sciences and Mathematics)
The theory of Banach contraction and the fixed point theorems of Schaefer are used to explain the behavior of positive solutions for the nonlinear differential equation of fractional order and the minimal values. Our main result is the presence and uniqueness of positive solution of the above equations. Finally, an example is given to illustrate our results.